2010
DOI: 10.1002/ajmg.a.33757
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genetic analysis of OEIS complex reveals no evidence for a recurrent microdeletion or duplication

Abstract: Omphalocele-exstrophy of the bladder-imperforate anus-spinal defects (OEIS) complex, or cloacal exstrophy (EC), is a rare constellation of malformations in humans involving the urogenital, gastrointestinal, and skeletal systems, and less commonly the central nervous system. Although OEIS complex is well-recognized in the clinical setting, there remains a significant lack of understanding of this condition at both the developmental and the genetic level. While most cases are sporadic, familial cases have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
1
26
1
2
Order By: Relevance
“…Although case reports for chromosomal abnormalities exist in literature, a microarray based study failed to identify any disease causing mutation in 14 candidate genes (Vlangos, 2011). The authors concluded that OEIS is unlikely to be caused by chromosomal abnormality and is most likely a complex disorder.…”
Section: Discussionmentioning
confidence: 88%
“…Although case reports for chromosomal abnormalities exist in literature, a microarray based study failed to identify any disease causing mutation in 14 candidate genes (Vlangos, 2011). The authors concluded that OEIS is unlikely to be caused by chromosomal abnormality and is most likely a complex disorder.…”
Section: Discussionmentioning
confidence: 88%
“…The occurrence rate of cloacal exstrophy variants is approximately 1/200,000-1/400,000 (2). No single environmental factor or genetic defect in the etiology of cloacal exstrophy has been identified (3,4). Many affected pregnancies are terminated, while those that reach full term typically result in infant mortality shortly after delivery (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The complex is estimated to occur in 1 of 200 000-400 000 pregnancies. Recent findings suggest that OEIS is a complex disorder from an etiological perspective, likely involving a combination of genetic and environmental predispositions (Vlangos et al 2010). Prenatal counseling of families with a diagnosis of OEIS complex is challenging (Tiblad et al 2008;Wax et al 2009).…”
Section: Introductionmentioning
confidence: 99%